1975
DOI: 10.1212/wnl.25.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord infarction due to minor trauma in children

Abstract: In two children, ages 22 months and 4 years, after slight trauma, flaccid weakness of both arms developed, followed by flaccid quadriplegia with sphincter involvement. No vertebral fracture or dislocation was found, myelograms were negative, and diagnosis was made only after the full clinical syndrome developed. Pathologic studies revealed ischemic infarction involving the cervical cord and low medulla in one patient, and central gray matter of low cervical cord in the other, without hematomyelia or external c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 0 publications
0
38
0
2
Order By: Relevance
“…Diseases of the abdominal aorta are rare in children, although there is one case of spinal cord ischemia with aortic dissection in an 18-year-old [40]. Minor trauma has also been associated with spinal cord infarction [41][42][43][44][45][46][47][48], but the exact etiology is not well understood. Pang et al propose that in children, the relatively less elastic spinal cord is strained inside of the more flexible spinal column during hyperflexion injuries, and that this may result in reactive vasospasm of spinal cord arteries leading to ischemia [11].…”
Section: Causes Of Spinal Cord Infarction In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases of the abdominal aorta are rare in children, although there is one case of spinal cord ischemia with aortic dissection in an 18-year-old [40]. Minor trauma has also been associated with spinal cord infarction [41][42][43][44][45][46][47][48], but the exact etiology is not well understood. Pang et al propose that in children, the relatively less elastic spinal cord is strained inside of the more flexible spinal column during hyperflexion injuries, and that this may result in reactive vasospasm of spinal cord arteries leading to ischemia [11].…”
Section: Causes Of Spinal Cord Infarction In Childrenmentioning
confidence: 99%
“…4 Hypotension Cardiac arrest [29] 6 Cardiac tamponade [30] 1 Arteriovenous malformation Vascular steal [32] 1 Mechanism unknown [31] 5 Thrombotic disorders Prothrombin variant [70,71] 2 Protein S deficiency [75] 1 Primary antiphospholipid syndrome [72] 1 Systemic lupus erythematosis [17,77] 3 Infectious disease Bacterial meningitis [53,[57][58][59][60][61][62][63][64][65][66][67] 15 Amebic menigoencephalitis [69] 1 Viral encephalitis [68] 1 Cerebellar herniation Metabolic encephalopathy [50] 3 Minor trauma [41][42][43][44][45][46][47][48] 18 Fibrocartilaginous embolism [1][2][3][85][86][87][88][89] 10 Cancer Anterior spinal artery thrombosis [76] 1 Atlanto-axial instability Achondroplasia [22] 1 I-cell disease [20] 1 Iatrogenic Sclerotherapy of esophageal varices [56] 1 Prolonge...…”
mentioning
confidence: 99%
“…Burke (1971) described two young children with perma nent flaccid paralysis following cord injury at T3 and T 4 segment. Ahmann et al (1975) reported two patients in whom spinal cord infarction due to minor trauma was confirmed by pathological study. One case was flaccid in the upper limbs only, while the second case was tetraplegic and areflexic.…”
Section: Discussionmentioning
confidence: 95%
“…Glasauer and Cares (1972) provide clinical information in two patients with visual examination of the cord in both. Ahmann et al (1975) provide a very clear history of the gradual evolution of tetraplegia in two children. The authors ascribe the spinal cord injury to a hyperextension mechanism in both children, but this is felt to be presumptive rather than proved.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The paper of Glasauer and Cares (1972) contributes two good case histories with, in one, macroscopic examination of the cord at laminectomy and, in the other, macroscopic and microscopic examina tion at autopsy. The paper of Ahmann et al (1975) is primarily concerned with the autopsy findings in two children, but there is some aetiological mechanistic information as well as clinical neurological information. The evidence available to the author includes that derived from three children who have recently been under his personal care, but, although the study of these children contributes a great deal in terms of the biomechanics of injury and clinical neurological presenta tion, it does not include any of the histological evidence which is necessary fully to understand the syndrome.…”
Section: Introductionmentioning
confidence: 99%